Anatomical and Round Breast Implants: How to Select and Indications for Use. Issue 2 (August 2015) - Hedén, Per; Montemurro, Paolo; Adams, William P.; Germann, Günter; Scheflan, Michael; Maxwell, G. Patrick
Abstract : Summary: Choosing between round and anatomical form-stable implants is a key decision in the process of breast augmentation. Anatomical devices have been subject to a number of misconceptions that have limited their use. However, in optimal clinical practice, the benefits and risks of both anatomical and round implants should be considered for any given patient. Patient and surgeon education is fundamental in ensuring that misunderstandings are addressed. The choice between anatomical and round devices should be based on a combination of patient desires, anatomy, and surgical history. This report presents experience-based recommendations on indications and contraindications for each type, and a proposed algorithm for decision making in clinical practice. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.